2014
DOI: 10.1111/jvh.12274
|View full text |Cite
|
Sign up to set email alerts
|

The impact of antihyperlipidemic drugs on the viral load of patients with chronic hepatitis C infection: a meta‐analysis

Abstract: Several studies investigating the role of statins and fibrates in chronic hepatitis C virus (HCV) infection offered so far conflicting evidence regarding the antiviral potency of these medications, whereas combination of these drugs with pegylated interferon and ribavirin improved in some trials therapeutic outcome. We conducted a literature search to identify trials that included monoinfected HCV patients, treated with statins or fibrates as monotherapy with the primary end point of our meta-analysis being th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
(78 reference statements)
1
6
0
Order By: Relevance
“…HNF4α down-regulation by bezafibrate dramatically reduced HCV secretion [ 235 ]. In line with this study, a meta-analysis showed that bezafibrate is associated with a reduction of viral load in chronically HCV-infected patients [ 168 ]. Moreover, in association with IFN and ribavirin, bezafibrate has been reported to reduce serum HCV RNA titers and to improve liver dysfunction [ 37 ].…”
Section: Htas To Inhibit Various Steps Of the Hcv Life Cyclesupporting
confidence: 67%
See 1 more Smart Citation
“…HNF4α down-regulation by bezafibrate dramatically reduced HCV secretion [ 235 ]. In line with this study, a meta-analysis showed that bezafibrate is associated with a reduction of viral load in chronically HCV-infected patients [ 168 ]. Moreover, in association with IFN and ribavirin, bezafibrate has been reported to reduce serum HCV RNA titers and to improve liver dysfunction [ 37 ].…”
Section: Htas To Inhibit Various Steps Of the Hcv Life Cyclesupporting
confidence: 67%
“…Notably, not all HMGCoA reductase inhibitors affect HCV replication, suggesting the existence of a different structure-activity relationship between the anti-HMGCoA reductase activity and the antiviral activity [ 166 ]. Fluvastatin is a statin that has been reported to increase the efficacy of IFN-based treatment in chronic HCV-infected patients [ 30 , 31 , 167 , 168 ]. Recent in vitro studies have provided novel insights into the mechanism of action of fluvastatin.…”
Section: Htas To Inhibit Various Steps Of the Hcv Life Cyclementioning
confidence: 99%
“…These properties may reduce or prevent hypercoagulability seen in the late stage of disease in many SARS-CoV-2 patients (34). A metanalysis has also suggested fenofibrate may be useful in the treatment of Hepatitis C infection (35). Lastly, we note a preprint from the group of Nahmias that has also suggested fenofibrate may have clinical effects against SARS-CoV-2 infection which depends on the PPARα mediated alterations in host cell metabolism (36).…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral potency of bezafibrate was confirmed in both Asian and European study populations. Interestingly, the significant clinical effect was found despite the failure of in vitro studies to demonstrate a significant effect [82].…”
Section: Antiviral Effectsmentioning
confidence: 99%